2020
DOI: 10.1093/cid/ciaa797
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Oropharyngeal Saliva for the Detection of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2)

Abstract: Background The coronavirus disease-2019 (COVID-19) pandemic has put tremendous pressure on the healthcare system worldwide. Diagnostic testing remained one of the limiting factors for early identification and isolation of infected patients. This study aimed to evaluate posterior oropharyngeal saliva (POPS) for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) detection among patients with confirmed or suspected COVID-19. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 19 publications
7
82
0
1
Order By: Relevance
“…The use of saliva to detect SARS-CoV-2 has been extensively analyzed by different authors, showing that saliva can be used as an alternative sample to nasopharyngeal swabs for COVID-19 molecular diagnosis(9, 10). The sensitivity found in their studies varied from 81% to 100% (11,12,(17)(18)(19)(20)(21). The majority of the studies were conducted with hospitalized patients presenting more severe clinical forms of the disease, is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint…”
Section: Discussionmentioning
confidence: 99%
“…The use of saliva to detect SARS-CoV-2 has been extensively analyzed by different authors, showing that saliva can be used as an alternative sample to nasopharyngeal swabs for COVID-19 molecular diagnosis(9, 10). The sensitivity found in their studies varied from 81% to 100% (11,12,(17)(18)(19)(20)(21). The majority of the studies were conducted with hospitalized patients presenting more severe clinical forms of the disease, is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint…”
Section: Discussionmentioning
confidence: 99%
“…(17,18) When only individuals with symptoms of < 9 days duration were included in the analysis, then the sensitivity of saliva in this study increased to 90%, which is consistent with findings of others. (5,7) This study was limited to adults. Additional studies are needed to determine the acceptability of saliva as an alternate specimen type in children.…”
Section: Downloaded Frommentioning
confidence: 99%
“…(2) Specifically, the shortage in nasopharyngeal swabs (NPS), the standard specimen collection device for the diagnosis of respiratory viral infections, has necessitated the investigation and employment of nasal mid-turbinate swabs, anterior nares swabs and even saliva as alternate specimens for the diagnosis of COVID -19 infection. (3)(4)(5) Several studies have investigated the use of saliva as a specimen for testing for SARS-CoV-2 with mixed results. (3,(5)(6)(7)(8)(9)(10)(11) We, therefore, undertook a direct NPS to saliva specimen comparison to provide further clarification regarding the use of saliva as a potential specimen for testing.…”
Section: Introductionmentioning
confidence: 99%
“…However, the specificity ranging from 97% to 100% suggests reliable detection limits of current assays for detecting the absence of SARS-CoV-2 viral loads in saliva samples. While 1 study showed that saliva could be considered for diagnosis in the early stages of disease due to the low costs (Wong et al 2020), a cost-effectiveness study should be performed to confirm this recommendation. There are at least 3 possible trajectories for SARS-CoV-2 to be present in saliva (Sabino-Silva et al 2020): 1) from the upper respiratory tract, when liquid droplets derived from these tissues could enter into the oral cavity; 2) from blood, when the virus could access the oral cavity via an exudate containing local proteins derived from the extracellular matrix and proteins derived from serum; and 3) from infection of the major and minor salivary glands, with the release of viral particles into the saliva via salivary ducts.…”
Section: Population-level Employable Rapid Testing Strategy: Advantagmentioning
confidence: 99%